An Analysis Of Self-Confidence In The Main Character Of I Feel Pretty (2018) Movie - Ibnu Subroto (Jurnal Ilmiah Multidisiplin, 2025)
Self-confidence is a crucial psychological attribute that significantly shapes how individuals view themselves and engage with their surroundings. It has a profound impact on personal motivation, decision-making processes, and overall self-development. This study explores the psychological factors influencing the self-confidence of the central character in the film I Feel Pretty, directed by Abby Kohn and Marc Silverstein. Employing a descriptive qualitative approach, the research centers on Renee Bennett and analyzes key scenes that reflect her progression in building self-confidence. The analysis reveals that Renee’s confidence is shaped by several core elements, including her self-concept, sense of self-worth, and lived experiences. The study further highlights the strategies she adopts to nurture her confidence, such as cultivating a positive self-image, embracing her capabilities, fostering optimistic thoughts, aligning actions with beliefs, and acknowledging her inner strengths. The results emphasize that while external beauty norms may remain fixed, personal transformation is possible through changes in self-perception. This research offers meaningful insights for those seeking to understand or enhance their own sense of confidence.